Structural and Dielectric Progression of 5 % Gd Doped BiFeO3 Nanoparticles Through Cr (2-8%) Doping (Journal of Engineering Science, 2022)
This study reports the structural modifications in undoped multiferroic BiFeO3 (bismuth ferrite or BFO) nanoparticles caused by doping at both the A-site (by 5% Gd) and B-site (by 2-8% Cr) and the resulting improvements in dielectric characteristics. Both un-doped and doped BFO nanoparticles were synthesized using the sol-gel technique and annealed at 600°C for crystallization. X-ray diffractometry (XRD) reveals a phase transition from rhombic (R3c) to orthorhombic (Pn21a). Field Emission Scanning Electron Microscopy (FESEM) study shows the production of nanoparticles with sizes ranging from 80 to 130 nm. Impedance analyzer experiments (100 Hz-10 MHz) show that the dielectric characteristics of doubly doped BFO are very stable over a wide frequency range. The dielectric permittivity of co-doped BFO decreases with Cr doping concentration up to x = 0.06 before reversing. The conductivity drops dramatically as the Cr content rises.Journal of Engineering Science 12(3), 2021, 101-110